A photosensitizing perylenediimide dye lights up cell nucleolus through visible light-mediated intracellular translocation. (December 2021) - Deng, Tao; Qi, Zhiwen; Wu, Yalan; Zhao, Jing; Wang, Lei; Peng, Danfeng; Zhang, Ying; Huang, Xin-an; Liu, Fang
Abstract: Intracellular redistribution of a photosensitizing fluorescent dye is concerned with its diagnostic and therapeutic features. To date such studies in this area are extremely scarce. Herein, a fluorescent photosensitizer PDI-1 with lysosome-targeting function has been prepared by functionalization of perylenediimide (PDI) with bis-tertiary amine groups. Fluorescence live cell imaging shows that PDI-1 can indeed target the lysosome, however, uncommon inter-organelle translocation was observed under continual visible light irradiation through a microscope. The cell nucleolus was subsequently lit up by PDI-1 in a photo-controllable manner. The imaging study using fixed cells confirmed that RNAs were the major target of PDI-1 in cell nucleolus. In addition, PDI-2 and PDI-3 were prepared by slightly modifying the structure of PDI-1. However, there is no obvious photo-induced redistribution observed on both PDI-2 and PDI-3. The result implies that even though tiny modification to the structure of a photosensitizer, the influence can be significant for its photobiological behavior. Graphical abstract: Image 1 Highlights: Inter-organelle translocation was observed upon imaging using PDI-1 a perylenediimide-tertiary amine photosensitizer (PS). PDI-1 offers a promising fluorescence probe for nucleolus imaging through a photo-controllable manner. Tiny modification to the structure of a PS can lead to great influence to its photobiological behaviors.